How Do Silent Trolls Become Overt Trolls? Fear of Punishment and Online Disinhibition Moderate the Trolling Path - Daniel Montez; Dam Hee Kim (Social Media + Society)
Digital media allow users the ability to engage in and be exposed to trolling. Although many people may enjoy the occasional opportunity to witness others being trolled, a relative minority directly troll others, those whom we can label overt trolls . Nevertheless, features afforded on social media and online communities (e.g., likes, upvotes) make it accessible for people to positively react to and support trolling, becoming supportive trolls , a potential steppingstone into overt trolling. In the theoretical contexts of social cognitive theory and the bystander effect, we advance a model in which enjoyment of observing trolling prompts supportive trolling, which could then lead to overt trolling. Analyses of data from an online survey conducted in the United States ( N  = 604) show the positive link between enjoyment of observing trolling and supportive trolling is stronger among individuals with higher fear of punishment, while the subsequent link between supportive and overt trolling is stronger among those with higher online disinhibition. Our findings hold implications in understanding the effects of trolling on social media audiences and how trolling can be performed in nuanced ways.